Beyond the Burden of History in Indigenous Australian Cinema: Understanding Production, Humour and Political Context through Nice Coloured Girls (1987) and The Sapphires (2012). Issue 1 (October 2019) - Pollock, Benjin
Abstract : How Indigenous Australian history has been portrayed and who has been empowered to define it is a complex and controversial subject in contemporary Australian society. This article critically examines these issues through two Indigenous Australian films: Nice Coloured Girls (1987) and The Sapphires (2012). These two films contrast in style, theme and purpose, but each reclaims Indigenous history on its own terms. Nice Coloured Girls offers a highly fragmented and experimental history reclaiming Indigenous female agency through the appropriation of the colonial archive. The Sapphires eschews such experimentation. It instead celebrates Indigenous socio-political links with African American culture, 'Black is beautiful', and the American Civil Rights movements of the 1960s. Crucially, both these films challenge notions of a singular and tragic history for Indigenous Australia. Placing the films within their wider cultural contexts, this article highlights the diversity of Indigenous Australian cinematic expression and the varied ways in which history can be reclaimed on film. However, it also shows that the content, form and accessibility of both works are inextricably linked to the industry concerns and material circumstances of the day. This is a crucial and overlooked aspect of film analysis and has implications for a more nuanced appreciation of Indigenous film as a cultural archive.